2021
DOI: 10.1364/ol.421999
|View full text |Cite
|
Sign up to set email alerts
|

17.8 fs broadband Kerr-lens mode-locked Yb:CALGO oscillator

Abstract: Pulses as short as 17.8 fs with a spectral bandwidth of 145 nm and central wavelength of 1118 nm have been generated from a Kerr-lens mode-locked Yb:CALGO oscillator. The oscillator operating at an average power of 26 mW and a repetition rate of 95.9 MHz is pumped by a cost-effective single-mode fiber coupled laser diode emitting 800 mW at 976 nm. The dispersion is compensated using a prism pair combined with broadband chirp mirrors. To the best of our knowledge, the pulse durations corresponding to approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As shown in Figure 3 , various hosts have been studied for this purpose such as sesquioxides Re 2 O 3 (Re stands for Y, Lu or Sc) [ 78 ] or CaGdAlO 4 (better known as CALGO) [ 79 , 80 ]. These materials typically have a much broader gain bandwidth compared to garnets and have already demonstrated very short pulse generation with bulk oscillators [ 81 ]. However, stringent requirements on the material quality of large sized samples, and good anisotropic thermal performance required for the disk geometry has so far generally limited their power scaling in ultrafast thin-disk operation beyond few tens of watts [ 79 , 82 ].…”
Section: Current Research Directions and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3 , various hosts have been studied for this purpose such as sesquioxides Re 2 O 3 (Re stands for Y, Lu or Sc) [ 78 ] or CaGdAlO 4 (better known as CALGO) [ 79 , 80 ]. These materials typically have a much broader gain bandwidth compared to garnets and have already demonstrated very short pulse generation with bulk oscillators [ 81 ]. However, stringent requirements on the material quality of large sized samples, and good anisotropic thermal performance required for the disk geometry has so far generally limited their power scaling in ultrafast thin-disk operation beyond few tens of watts [ 79 , 82 ].…”
Section: Current Research Directions and Challengesmentioning
confidence: 99%
“…Later on, pulse durations as short as 62 fs were demonstrated with an average output power of 5.1 W [ 80 ]. With KLM, pulses as short as 30 fs has been demonstrated which is shortest pulses directly from a thin-disk oscillator [ 61 ], however, the average output power was limited to a very low 150 mW [ 61 ] which can also be reached in the bulk geometry [ 81 , 87 ]. Several difficulties have made power scaling of this material more difficult than initially expected: on the one hand this material is uniaxial therefore; absorption, emission as well as thermal properties are not anisotropic, which limits power scaling with good beam quality as required for modelocking.…”
Section: Current Research Directions and Challengesmentioning
confidence: 99%
“…To overcome the spectral and power limitations of collinearly pumped ultrashort lasers, Layaye et al designed a cross-polarized pumping regime and obtained 31 fs pulses with 389 mW of average power and 29% efficiency recently [109]. Newly, Wang et al delivered pulses with the shortest duration (4.8 optical cycles) ever reported for a KLM Yb-bulk laser [110]. By introducing two broadband chirped mirrors and a prism pair to regulate the intracavity dispersion, as shown in Figure 4d, 17.8 fs pulses with 26 mW of average power at 95.9 MHz were triggered, indicating compelling performance brought by this special crystal.…”
Section: Ultrashort Pulses With Kerr-lens Mode-locking In Yb:calgo Lasersmentioning
confidence: 99%
“…(7) Yb:CALGO enabled direct emission of watt-level 10-gigahertz pulses from a simple and small straight laser cavity [99]. (8) Yb:CALGO created the shortest pulses with time duration of 17.8 fs in a Kerr-lens mode-locked architecture [110]. (9) Yb:CALGO optical frequency comb created the narrowest free-running CEO linewidth as 1.6 kHz and a comb optical linewidth narrower than 28 kHz in 1 ms observation time at 1064 nm [118].…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…Using a Yb:CALGO crystal, 96 fs pulses were obtained with average power of 12.5 W, which is the highest output power from sub-100-fs Yb-doped oscillators [9] . In 2021, a Yb:CALGO oscillator delivering 17.8 fs pulses with 26 mW of average power was reported [16] . Moreover, Tian et al of Xidian University reported on the 98 fs Yb:CALYO oscillator with 10 W of average output power at 81 MHz based on Kerr-lens mode-locking [17] .…”
Section: Introductionmentioning
confidence: 99%